Trends in Outpatient Cervical Spine Surgery: Are There Emerging Disparities?. Issue 9 (1st May 2023) - Amen, Troy B.; Bovonratwet, Patawut; Rudisill, Samuel S.; Barber, Lauren A.; Jordan, Yusef J.; Chatterjee, Abhinaba; Mok, Jung K.; Varady, Nathan H.; Qureshi, Sheeraz A.
Abstract : Study Design: Retrospective analysis on prospectively collected data. Objective: The purposes of this study were to (1) assess disparities in relative utilization of outpatient cervical spine surgery between White and Black patients from 2010 to 2019 and (2) to measure how these racial differences have evolved over time. Summary of Background Data: Although outpatient spine surgery has become increasingly popularized over the last decade, it remains unknown how racial disparities in surgical utilization have translated to the outpatient setting and whether restrictive patterns of access to outpatient cervical spine procedures may exist. Methods: A retrospective cohort study from 2010 to 2019 was conducted using the National Surgical Quality Improvement Program database. Relative utilization of outpatient (same-day discharge) for anterior cervical discectomy and fusion (OP-ACDF) and cervical disk replacement (OP-CDR) were assessed and trended over time between races. Multivariable regressions were subsequently utilized to adjust for baseline patient factors and comorbidities. Results: Overall, Black patients were significantly less likely to undergo OP-ACDF or OP-CDR surgery when compared with White patients ( P <0.03 for both OP-ACDF and OP-CDR). From 2010 to 2019, a persisting disparity over time was found in outpatient utilization for both ACDF and CDR ( e.g. White vs. Black OP-ACDF: 6.0% vs. 3.1% in 2010 compared with 16.7% vs. 8.5% in 2019). These results held in all adjusted analyses. Conclusions: To our knowledge, this is the first study reporting racial disparities in outpatient spine surgery and demonstrates an emerging disparity in outpatient cervical spine utilization among Black patients. These restrictive patterns of access to same-day outpatient hospital and surgery centers may contribute to broader disparities in the overall utilization of major spine procedures that have been previously reported. Renewed interventions are needed to both understand and address these emerging inequalities in outpatient care before they become more firmly established within our orthopedic and neurosurgery spine delivery systems.